2019
DOI: 10.3168/jds.2018-14911
|View full text |Cite
|
Sign up to set email alerts
|

Methane prediction based on individual or groups of milk fatty acids for dairy cows fed rations with or without linseed

Abstract: Milk fatty acids (MFA) are a proxy for the prediction of CH 4 emission from cows, and prediction differs with diet. Our objectives were (1) to compare the effect of diets on the relation between MFA profile and measured CH 4 production, (2) to predict CH 4 production based on 6 data sets differing in the number and type of MFA, and (3) to test whether additional inclusion of energy-corrected milk (ECM) yield or dry matter intake (DMI) as explanatory variables improves predictions. Twenty dairy cows were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
2
8
0
1
Order By: Relevance
“…The two intermediates mentioned, but not the terminal product C18:0, are considered valuable to human health. Linseed has been reported to enhance both the n-3 FA and biohydrogenation intermediates [8,10,11]. The effects of linseed on the FA profile of milk fat in our study were similar at both the individual and group levels (bulk milk), indicating that changes can be clearly recovered in a few bulk milk samples obtained from linseed-fed herds of dairy cattle.…”
Section: Effects Of Linseed Supplementation On Milk Composition At Thsupporting
confidence: 75%
See 3 more Smart Citations
“…The two intermediates mentioned, but not the terminal product C18:0, are considered valuable to human health. Linseed has been reported to enhance both the n-3 FA and biohydrogenation intermediates [8,10,11]. The effects of linseed on the FA profile of milk fat in our study were similar at both the individual and group levels (bulk milk), indicating that changes can be clearly recovered in a few bulk milk samples obtained from linseed-fed herds of dairy cattle.…”
Section: Effects Of Linseed Supplementation On Milk Composition At Thsupporting
confidence: 75%
“…This difference in response to extruded linseed could have resulted from the different forage type (corn vs. grass silage) and the forage-to-concentrate ratio used in the experiments. Accordingly, the effect of moderate levels of linseed on CH 4 were weaker in the studies of Engelke et al [10] and Martin et al [6], when exchanging corn silage with grass silage and when reducing the concentrate proportion from 50% to 40%, respectively. This is consistent with the findings of Machmüller et al [35], who found that using a lower forage-to-concentrate proportion led to lower methane-mitigating effects of medium-chain FA.…”
Section: Effects Of Linseed On Methane Emission At Group and Individumentioning
confidence: 91%
See 2 more Smart Citations
“…Via vetzuurprofielen van de melk blijkt een voorspelling van de methaanuitstoot mogelijk te zijn (Dijkstra et al, 2011). Dit is ook afhankelijk van de samenstelling van het voer (Engelke et al, 2019).…”
Section: Vettenunclassified